Personal data protection and liability for damage in the field of the internet of things - Некіт, Катерина Георгіївна; Некит, Екатерина Георгиевна; Nekit, Ekaterina G.; Некіт, К. Г.; Nekit, Kateryna H.; Колодін, Денис Олексійович; Колодін, Д. О.; Колодин, Денис Алексеевич; Kolodin, Denys O.; Федоров, Валентин Андрійович; Федоров, В. А.; Федоров, Валентин Андреевич; et al. (Bucharest Academy of Economic Studies, 2020)
This article analyzes the concept and legal issues of the Internet of Things to explore whether the existing legal framework is appropriate to deal with this new phenomenon. It examines the system of legal issues in the field of the Internet of Things and the ways of their solution. The attention is paid to the personal data protection issue. The conclusion is made about the necessity to ensure the realization of GDPR provisions concerning privacy outside the European Union, which is possible by the conclusion of international agreements with non-EU countries. The article also considers how it is possible to deal with damage caused by the Internet of Things. This takes into account conditions of compensation of damage caused by IoT devices. The necessity of selfregulation in the field of the Internet of Things for ensuring information security and preventing damage caused by the Internet of Things is emphasized. This would be possible in case of close cooperation between technology companies and civil society. Such an approach would minimize government intervention in this area, which would contribute to the rapid development of innovative technologies.

В этой статье анализируется концепция и правовые проблемы "Интернета вещей", чтобы выяснить, уместна ли существующая законодательная база для решения этого нового явления. В ней рассматривается система правовых вопросов в области "Интернета вещей" и пути их решения. Внимание уделяется вопросам защиты персональных данных. Сделан вывод о необходимости обеспечить реализацию положений GDPR в отношении конфиденциальности вне Европейского Союза, что возможно путем заключения соглашений со странами, не входящими в ЕС. В статье также рассматривается, как можно бороться с убытками, причиненными "Интернетом вещей". Учитываются условия возмещения вреда, причиненного устройствами IoT. Подчеркивается необходимость саморегулирования в сфере "Интернета вещей" для обеспечения информационной безопасности и предотвращения вреда, причиненного "Интернетом вещей". Это было бы возможным в случае тесного сотрудничества между технологическими компаниями и гражданским обществом. Такой подход позволит минимизировать государственное вмешательство в эту сферу, что будет способствовать быстрому развитию инновационных технологий.

У цій статті аналізується концепція та правові проблеми "Інтернету речей", щоб з’ясувати, чи доречна існуюча законодавча база для вирішення цього нового явища. У ній розглядається система правових питань у галузі "Інтернету речей" та шляхи їх вирішення. Увага приділяється питанням захисту персональних даних. Зроблено висновок про необхідність забезпечити реалізацію положень GDPR щодо конфіденційності за межами Європейського Союзу, що можливо шляхом укладення міжнародних угод із країнами, що не входять до ЄС. У статті також розглядається, як можна боротися зі збитками, заподіяними "Інтернетом речей". Враховуються умови відшкодування шкоди, заподіяної пристроями IoT. Підкреслюється необхідність саморегулювання у сфері "Інтернету речей" для забезпечення інформаційної безпеки та запобігання шкоди, завданої "Інтернетом речей". Це було б можливим у разі тісної співпраці між технологічними компаніями та громадянським суспільством. Такий підхід дозволить мінімізувати державне втручання у цю сферу, що сприятиме швидкому розвитку інноваційних технологій.
Nekit K. Personal data protection and liability for damage in the field of the internet of things / K. Nekit, D. Kolodin, V. Fedorov // Juridical Tribune (Tribuna Juridica). – V. 10 (1). – Bucharest Academy of Economic Studies, Law Department, 2020. – P. 80-93.
Keywords: Internet of Things; GDPR; personal data protection; information security; privacy; compensation of damage; "Інтернет речей"; GDPR (Загальний регламент щодо захисту персональних даних); захист персональних даних; інформаційна безпека; конфіденційність; відшкодування шкоди; "Интернет вещей"; GDPR (Генеральный регламент о защите персональных данных); защита персональных данных; информационная безопасность; конфиденциальность; возмещение ущерба; Research Subject Categories::LAW/JURISPRUDENCE